Correlation between Endometrial Vascular Endothelial Growth Factor Expression and Pregnancy Outcome of Frozen–Thawed Embryo Transfer in Patients with Repeated Implantation Failure - Rui Jin; Wenye Ma; Dawei Tang; Fang Liu; Gang Bai; Mengmeng Reng (Applied Bionics and Biomechanics)
Objective. Vascular endothelial growth factor (VEGF) is a well-known angiogenic factor that is essential to numerous physiological and pathological processes. VEGF also contributes to embryo implantation by promoting embryo development, enhancing endometrial receptivity (ER), and promoting interactions between the endometrium and developing embryo. Changes in VEGF expression are linked to repeated implantation failure (RIF). Control endometrial tissues demonstrated an increase in VEGF expression during the implant window period, which promoted early villous vascularization and embryo implantation. The purpose of this study is to investigate the relationship between RIF and the expression of ER markers, such as VEGF during the implantation window stage. Methods. The Yinchuan Maternal and Child Health Hospital collected 192 cases of FET endometrial tissues in the implantation window stage between January 2019 and December 2021. Immunohistochemistry was utilized to measure the levels of VEGF expression in patients with RIF (RIF group, n=82) and patients with a successful pregnancy (control group, n=110). The relationship between VEGF and the RIF group was analyzed using Spearman’s correlation coefficient. Results. VEGF levels were significantly lower during the implantation window stage (P<0.05). Conclusion. VEGF was expressed in planting window stage. The decrease of VEGF during the implantation window was correlated with RIF.